MANAJEMEN KEPALA SEKOLAH DALAM MENGELOLA DANA BANTUAN OPERASIONAL SEKOLAH (BOS) UNTUK MENINGKATKAN MUTU PENDIDIKAN DI SD NEGERI - Fadlika, Fadlika; Siraj, Siraj; Mukhlisuddin, Mukhlisuddin (Research and Development Journal of Education, 2024)
This research aims to analyze the planning (budgeting), implementation (accounting) and monitoring (auditing) of BOS funds in improving the quality of education in Public Elementary Schools in Bintang District, Central Aceh Regency, to analyze the strategies and obstacles of school principals in managing BOS funds to improve the quality of education. This research method uses descriptive research with qualitative analysis. This research will be carried out at SD Negeri Bintang District, Central Aceh Regency. Data collection in this research used three techniques, namely interviews, observation and documentation. The research results show that 1) planning (budgeting) by making a School Activity and Budget Plan (RKAS) which is adjusted to the School Work Plan (RKS). The preparation of the plan begins with identifying needs and determining the priority scale or school needs. 2) In the implementation process (accounting), each use of BOS funds follows the technical guidelines that have been determined. One of them is that every transaction/expenditure is recorded or recorded in a special book by the treasurer as the manager of BOS funds, 3) The monitoring (auditing) process is carried out by the entire school community such as the principal, representatives, treasurer, committee and teachers. Apart from that, external audits are directly carried out by BOS management at the Education Office. 4) The principal's strategy in managing BOS funds to improve the quality of education at the Public Elementary School in Bintang District, Central Aceh Regency is carried out with planning that prioritizes school needs/priorities which emphasizes improving the quality of education. by providing learning facilities and media as well as developing teacher competency.